1995
DOI: 10.1007/bf01409600
|View full text |Cite
|
Sign up to set email alerts
|

The proactive model of school counselling

Abstract: Abstract. This article discusses the prevalent crisis in secondary school counselling and suggests a new model to change the role, priorities, and activities of a school counsellor from a peripheral to the central position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Schmidt suggested that guidance is a role shared by everyone who works in schools and cares about children. At a time when school counseling as a profession is struggling for recognition as an essential service (Sandhu & Portes, 1995), it is important for school counselors to describe themselves and their services in terminology that reflects their unique contribution and specialization. Schmidt also cautioned that the term counseling be perceived in the broadest of contexts to include a wide selection of services, not just remedial or one-to-one relationships.…”
Section: Developmental Guidance and Counselingmentioning
confidence: 99%
“…Schmidt suggested that guidance is a role shared by everyone who works in schools and cares about children. At a time when school counseling as a profession is struggling for recognition as an essential service (Sandhu & Portes, 1995), it is important for school counselors to describe themselves and their services in terminology that reflects their unique contribution and specialization. Schmidt also cautioned that the term counseling be perceived in the broadest of contexts to include a wide selection of services, not just remedial or one-to-one relationships.…”
Section: Developmental Guidance and Counselingmentioning
confidence: 99%
“…As the study developed, our subject seemed to epitomize what had been noted in the literature regarding effective school counseling, and these references became the sensitizing concepts that guided our study. Counselors, according to Sandhu and Portes's (1995) proactive model of school counseling, need to move from a peripheral to a central position in regard to school improvement, grounded by a conceptual blueprint, and, according to George (1986), with high-quality leadership and a sense of mission. Most of their time should be spent in direct delivery of services, not administrative, clerical, and paraprofessional tasks (Baker, 2000), and they need to be accountable, demonstrating that their work makes a positive difference in the lives of students (Gysbers & Henderson, 1994;Baker, 2000).…”
Section: Sensitizing Conceptsmentioning
confidence: 99%
“…Most of their time should be spent in direct delivery of services, not administrative, clerical, and paraprofessional tasks (Baker, 2000), and they need to be accountable, demonstrating that their work makes a positive difference in the lives of students (Gysbers & Henderson, 1994;Baker, 2000). Counselors are also encouraged to be involved in personal and professional development in the interest of enhancing competence and effectiveness (Sandhu & Portes, 1995). Wiggins and Giles (1984) and Wiggins and Weslander (1986) found that high self-esteem in counselors was important to counselor effectiveness.…”
Section: Sensitizing Conceptsmentioning
confidence: 99%
“…Over the past few years, there has been a call for school counselors to redefine and expand their roles (Anderson & Reiter, 1995;House & Martin, 1998;Napierkowski & Parsons, 1995;Paisley & Borders, 1995). They have been admonished to assume a more activist role and move from a peripheral to a central position (Osborne et al, 1998;Sandhu & Portes, 1995) in the interest of creating a climate conducive to student learning (Kaplan & Geoffroy, 1990). Building and maintaining partnerships is one way that counselors can assume the mantle of educational leadership within their schools.…”
mentioning
confidence: 99%